Influencers, brands and sexual health promotion: The case of Durex Spain on TikTok - Zomeño-Jiménez, Daniel; Tur-Viñes, Victoria; Cuesta-Martínez, Carlos (Revista Española de Comunicación en Salud, 2025)
Introduction: This research explores the case of Durex Spain’s branded content strategy on TikTok, specifically through its sexual advice series “Hay tema.” This project has been recognized and awarded at the TikTok Awards Spain (2022), Inspirational Awards (2023), BCMA Spain Awards (2023), and National Marketing Awards (2024). Objectives: The study aims to analyze the profile and characteristics of the influencers involved, their impact in terms of engagement, and the content formats used. Methodology: A quantitative-qualitative methodological triangulation has been adopted, combining content analysis with in-depth interviews. Results: The findings indicate that the reach and interaction of the content are not influenced by the influencer’s gender or their original audience, but rather by the interest generated by the topic of each post. Additionally, Durex demonstrates an adaptation to common content types and narratives on the platform, such as explanatory videos, video podcasts, and street interviews. Conclusion: The conclusions emphasize the importance for brands with educational goals to adapt their digital strategies to the preferences of younger generations. This involves adopting an accessible tone and popular formats that integrate infotainment and credibility.
Keywords: Branded Content; Influencers; TikTok; Generation Z; Durex; Generation Alpha; Sex education